2016
DOI: 10.1007/s00405-016-3896-6
|View full text |Cite
|
Sign up to set email alerts
|

Auditory phenotype in Stickler syndrome: results of audiometric analysis in 20 patients

Abstract: Hearing loss in Stickler syndrome has received little attention due to the often more disabling ocular, orofacial and skeletal manifestations. Estimates suggest a global prevalence of sensorineural hearing loss (SNHL) ranging from 50 % to about 100 % though, depending on the underlying Stickler genotype. By performing extensive audiometric analysis in Stickler patients, we aimed to further elucidate the auditory phenotype. Twenty molecularly confirmed Stickler patients (age 10-62 year), of whom sixteen with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Patients with collagenopathies that include hearing impairment due to deleterious variants in COL11A1 (STL2 and Marshall syndrome) and COL11A2 (STL3) also show remarkably similar types of audiograms. 34 36 The results of psychophysical tests at suprathreshold levels in DFNA8/12, DFNA13, and STL3 ( COL11A2 ) patients revealed that the type of hearing impairment is compatible with intracochlear conduction loss. 36 38 This is in line with the notion that disease-causing variants in COL11A2 affect tectorial membrane function.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with collagenopathies that include hearing impairment due to deleterious variants in COL11A1 (STL2 and Marshall syndrome) and COL11A2 (STL3) also show remarkably similar types of audiograms. 34 36 The results of psychophysical tests at suprathreshold levels in DFNA8/12, DFNA13, and STL3 ( COL11A2 ) patients revealed that the type of hearing impairment is compatible with intracochlear conduction loss. 36 38 This is in line with the notion that disease-causing variants in COL11A2 affect tectorial membrane function.…”
Section: Discussionmentioning
confidence: 99%
“…Carry out content screening processing on the sorted electronic medical record data [8]. According to the different research purposes, different medical records in the electronic medical records are selected, and different attribute information in the medical records is screened according to different target attributes.…”
Section: Strategy Of Diabetes Riskmentioning
confidence: 99%
“…Hearing loss is a common feature of SS [ 2 , 5 , 28 , 31 , 36 , 37 ]. The most common form of hearing loss is pure sensorineural hearing loss, with increasing prevalence with age [ 36 , 38 ].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Mixed sensorineural and conductive hearing loss and purely conductive hearing loss may also be seen, more commonly affecting children or those with history of palatal defects [ 5 , 36 ]. Individuals with STL1 generally exhibit a mild to moderate sensorineural hearing loss that affects the higher frequencies [ 36 , 37 , 38 ]. In contrast, individuals with STL2 tend to have more pronounced hearing loss that is more apparent at younger ages [ 36 , 37 , 38 ].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation